HUBUNGAN ANTARA DUKUNGAN SOSIAL DAN KEPERCAYAAN DIRI DENGAN MOTIVASI UNTUK SEMBUH PADA NARAPIDANA KASUS NARKOBA DI LEMBAGA PEMASYARAKATAN KLAS. II A MEDAN - Shirly, Aulia; Prihadiansyah, Khansa Deryqa (Journal of Mental Health and Social Rehabilitation, 2025)
Drug abuse can happen to anyone, both women and men, regardless of age, social status or educational background. Convicts of drug abuse cases, to be able to recover would require motivation, such as Social Support and Self Confidence. Motivation is a driving force from within and within a person's heart to do or achieve a goal. The existence of social support aimed at convicts aims to enable prisoners to be able to face an unpleasant life and be able to adjust well. Building self-confidence is a form of belief in the best ability that comes from oneself, which is sufficient to be aware of one's abilities. This study aims to determine the relationship between social support and motivation to recover in drug cases inmates at the Class II A Medan Women's Correctional Institution. This study aims to determine the relationship between social support and self confidence with motivation to recover in drug convicts at the Class II A Women's Penitentiary in Medan. The benefits of this research provide knowledge to further deepen knowledge in the field of community empowerment and provide knowledge and understanding to the heads and officers of correctional institutions, namely to be able to provide social support for prisoners who are serving a criminal period. Based on the results of research with respondents of Class II A Medan Women's Correctional Institution, it was concluded that there was a significant relationship between Social Support and Self-Confidence on motivation to recover. In the simultaneous multiple correlation analysis showing the value of Sig F Square, it is concluded that the relationship between Spatial Support and Confidence on motivation to recover is 75,1%. The importance of the role of social support and self-confidence in inmates' self-development so that self-motivation arises for greater recovery.